IMPLEMENTASI MODEL ATIK TERHADAP KEMAMPUAN LITERASI MATEMATIKA PADA MATERI PECAHAN KELAS V SD - Rahmadhani, Anindhita Putri Syahria; Mariyam; Sumarli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether or not there is a difference in students' mathematical literacy skills before and after the ATIK Model (Observe, Imitate, Do) is applied to fractional material for grade V; Improvement in students' mathematical literacy skills after the ATIK model is applied; and the Implementation of the ATIK model on mathematical literacy skills. The type of research used is quantitative Pre-experimental research in the form of one group pretest posttest. This research was conducted at SDN 06 Semparuk. The research population was all fifth grade students of SDN 06 Semparuk with a sampling technique in the form of saturated sampling technique totaling 18 students. The data collection technique used test and non-test measurement techniques. The data analysis technique is quantitative data analysis and statistics. The results of the study can be concluded that: (1) There is a difference in students' mathematical literacy skills before and after the ATIK model is applied between the pretest class and the posttest class that were given treatment, namely using t-test analysis with a P value calculation of 0.01 <0.05.; (2) There is an increase in students' mathematical literacy skills in the application of the ATIK model. The application of the ATIK model in learning fractional material can be carried out well.; (3) The implementation of the ATIK model on students' mathematical literacy skills was an average of 84% with a very good category.